Subjective and critical analisis of the contents of the taught topographical anatomy in the Surgery Department of the Veterinary Medicine College and Zootecny of São Paulo University and a proposal of suitability based on the contemporary professional reality - Lazinho, Raquel Cristina; Miglino, Maria Angélica; Ferreira, Jussara Rocha (Brazilian Journal of Veterinary Research and Animal Science, 2004)
Our purpose was evaluate the present, through the case study, where we analyzed the Program of the Discipline of Topographical Anatomy and we interpreted the extension, depth and adaptation of these contents, starting from the observance of the interest or not of minister, as base for the clinic, surgery, technologies and others areas of performance in the generalist veterinarian graduation, where the anatomy makes herself present. We tried more and more to contemplate on the context of such teaching in relationship to the demands of the labor market, to thedemands competitive and unstable. Through the documental analysis and interviews structured, we arrived to a consent that would be necessary to adapt the information among the basic and professional cycles, to implant a form of active education, where the student builds its learning and evaluation, using a pedagogic proposal that includes the educational technologies and the university extension.